ANALISIS KEANDALAN BANGUNAN GEDUNG (STUDI KASUS: BANGUNAN GEDUNG REKTORAT UNIVERSITAS MAHASARASWATI DENPASAR) - TJOKORDA ISTRI PRAGANINGRUM; NI LUH MADE AYU MIRAYANI PRADNYADARI; PUTU OCHA MAYA FIRANTHI (Universitas Mahasaraswati K. Mataram, 2023)
The Building in situations and conditions until now there are still some that have experienced partial or complete collapse due to several causes, namely natural disasters, converted building functions that cause undue pressure / load, or structural failures or errors. In this regard, it is desirable that there will be a reliability check on the building. The building studied in this study is the Rectorate Building of Mahasaraswati University Denpasar. In this case, to evaluate the reliability of the Building, an analysis was carried out with interviews and questionnaires with interview samples, namely 14 speakers and questionnaires, namely 34 respondents. In this study using descriptive research methods with quantitative and qualitative approaches. Factors that affect the reliability of the rectorate building of Mahasaraswati University Denpasar include architecture, structure, utility and fire protection, accessibility, building arrangements and the environment. The results of the evaluation of the level of reliability of this building include architecture, namely 87% which includes less reliable (75 - < 95%), structures which are 96% which include reliable (95 - 100%), utilities and fire protection which are 86% which include unreliable (< 95 %), accessibility which is 82% which includes less reliable (75 - < 95%), and building and environmental arrangements which are 57% which include unreliable (< 75%). The total reliability value is 82% where the building of the Rectorate Building of Mahasaraswati University Denpasar is less reliable (75 - < 95%)